Chern classes of integral submanifolds of some contact manifolds - Gheorghe Pitiş (International Journal of Mathematics and Mathematical Sciences)
A complex subbundle of the normal bundle to an integral submanifold of the contact distribution in a Sasakian manifold is given. The geometry of this bundle is investigated and some results concerning its Chern classes are obtained.